Optimal contracting of pension incentive: Evidence of currency risk management in multinational companies - Jun Chen; Yun Guan; Ivy Tang (Journal of Risk and Financial Management, 2020)
Using a large sample of multinational companies (MNCs), this paper intends to explore whether executives' pension incentives will function as a mechanism of optimal contracting in motivating firm risk management. We find that granting more pension to executives is significantly related to the higher likelihood and intensity of currency hedging strategies in MNCs. This suggests that pension incentive should promote executives to more actively manage firms' risk. Such a positive relationship is robust to endogeneity and is more prominent in firms with strong shareholder power. We further explore the contribution of currency hedging induced by pension incentives to shareholder value. Supporting the hypothesis of optimal contracting, our results indicate that pension incentives play an important role in reconciling managerial risk preference and shareholder value creation.
Keywords: 330; currency hedging; firm value; multinational companies; pension incentive